2021
DOI: 10.30587/umgeshic.v1i2.3433
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Emotional Intelligence on the Quality of Administrative Service

Abstract: This study aims to examine the effect of Emotional Intelligence on the Quality of Administrative Services at the University of Muhammadiyah Gresik. Emotional intelligence is the ability of an individual to recognize himself in terms of controlling or managing emotions towards himself and others or the surrounding environment through skills of self-awareness, self-control, self-motivation, empathy, and social skills or abilities so that it can help a person achieve certain goals. according to what is expected. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Organizational Citizenship Behavior factors can also affect service quality. However, several studies have shown opposite results, such as research by research (Agustin et al, 2015) showing emotional intelligence does not affect service quality. Research (Lustono et al, 2021) shows no effect of organizational commitment on service quality.…”
Section: Introductionmentioning
confidence: 98%
“…Organizational Citizenship Behavior factors can also affect service quality. However, several studies have shown opposite results, such as research by research (Agustin et al, 2015) showing emotional intelligence does not affect service quality. Research (Lustono et al, 2021) shows no effect of organizational commitment on service quality.…”
Section: Introductionmentioning
confidence: 98%